Mediators linking gut microbiota and sporadic Creutzfeldt–Jakob disease: a Mendelian randomization study - Jie Shao; Tengfei Su; Jinyan Wang; Xiang Yin; Yue Lang; Yuxin Fu; Li Cui (AMB Express)
Abstract While gut microbiome associations with sporadic Creutzfeldt–Jakob disease (sCJD) are recognized, causal mechanisms and mediation via cerebrospinal fluid (CSF) metabolites remain unestablished. Using bidirectional Mendelian randomization (MR) with mediation analysis and integrating genome-wide association study (GWAS) summary statistics from gut microbiota (​​composition in the FINRISK 2002 prospective cohort, n = 5,959​​), CSF metabolites (from the Wisconsin Alzheimer's Disease Research Center ​​Registry and Wisconsin Registry for Alzheimer's Prevention​​, n = 291), and sCJD case–control data (5,208 cases vs. 511,675 controls), we identified five microbial taxa influencing sCJD risk. Protective effects were observed for the family Atopobiaceae [odds ratio (OR) = 0.527, 95% confidence interval (CI) = 0.321–0.864, P = 0.011], the species Enterococcus faecalis (OR = 0.647, 95% CI = 0.427–0.980, P = 0.040), and the genus Lactobacillus (group B) (OR = 0.768, 95% CI = 0.602–0.981, P = 0.035). Conversely, the species Bacteroides eggerthii (OR = 1.228, 95% CI = 1.027–1.468, P = 0.025) and the order Chloroflexales (OR = 3.455, 95% CI = 1.214–9.835, P = 0.020) were pathogenic. Mediation analysis revealed that S-methylcysteine mediates 8.8% of ​​the effect of order Chloroflexales on sCJD risk​​, establishing it as a significant biological mediator in this pathogenic pathway. These findings provide novel biomarkers for early sCJD risk stratification, identify ​​the family Atopobiaceae, the species Enterococcus faecalis, and the genus Lactobacillus (group B)​​ as probiotic candidates for primary prevention, reveal S-methylcysteine pathway modulation as therapeutic entry points, and establish mechanistic foundations for disrupting gut-CSF transmission​​ in prion diseases. Graphical abstract Bidirectional causal relationship between the gut microbiome and sporadic Creutzfeldt–Jakob disease (sCJD). Prefixes f., g., s., and o. in taxon labels denote family, genus, species, and order, respectively. The analysis encompassed 471 bacterial taxa across 11 phyla, 19 classes, 24 orders, 62 families, 146 genera, and 209 species. Abbreviations: WADRC, Wisconsin Alzheimer’s Disease Research Center; WRAP, Wisconsin Registry for Alzheimer’s Prevention; CSF, cerebrospinal fluid.